IMPLEMENTASI SUPERVISI PENDIDIKAN DI SEKOLAH DASAR - anjarsari, riana; Mahroso, Doloh (Universitas Islam Negeri (UIN) Jurai Siwo Lampung, 2024)
This research aims to provide information regarding the implementation of educational supervision at SD IT Wahdatul Ummah Metro, Lampung, SDI Darul Amin Hidayatullah, Kota Gajah, Lampung Tengah, and SD Negeri 6 Metro Timur, Metro. This research uses descriptive qualitative research. Data obtained through structured interviews and direct observation. The results of the research show that educational supervision has been running in elementary schools in Metro and Central Lampung using classroom observations, class visits, monitoring, training online nor offline, seminar, workshop, teacher portfolio, KKG, and webinars.